Maximising renewable hosting capacity in electricity networks - Sun, Wei (The University of Edinburgh, 2015)
The electricity network is undergoing significant changes in the transition to a low carbon system. The growth of renewable distributed generation (DG) creates a number of technical and economic challenges in the electricity network. While the development of the smart grid promises alternative ways to manage network constraints, their impact on the ability of the network to accommodate DG – the ‘hosting capacity’- is not fully understood. It is of significance for both DNOs and DGs developers to quantify the hosting capacity according to given technical or commercial objectives while subject to a set of predefined limits. The combinational nature of the hosting capacity problem, together with the intermittent nature of renewable generation and the complex actions of smart control systems, means evaluation of hosting capacity requires appropriate optimisation techniques. This thesis extends the knowledge of hosting capacity. Three specific but related areas are examined to fill the gaps identified in existing knowledge. New evaluation methods are developed that allow the study of hosting capacity (1) under different curtailment priority rules, (2) with harmonic distortion limits, and (3) alongside energy storage systems. These works together improve DG planning in two directions: demonstrating the benefit provided by a range of smart grid solutions; and evaluating extensive impacts to ensure compliance with all relevant planning standards and grid codes. As an outcome, the methods developed can help both DNOs and DG developers make sound and practical decisions, facilitating the integration of renewable DG in a more cost-effective way.
Keywords: active network management; distributed generation; principle of access; harmonics; energy storage; DG curtailment